2018
DOI: 10.18203/2394-6040.ijcmph20180229
|View full text |Cite
|
Sign up to set email alerts
|

Health care seeking behavior of parents of under five in District Kanga, Himachal Pradesh

Abstract: INTRODUCTIONThere is growing recognition, in both developed and developing countries, that providing education and knowledge at the individual level is not sufficient in itself to promote a change in behavior. Utilization of the formal system in case of illness is also known as health care seeking behavior and the process involved in achieving a health state has been termed as health seeking behavior. Studies demonstrate that the decision to engage with a particular medical channel is influenced by a variety o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
3
2
Order By: Relevance
“…10 Majority from urban 87% practiced self-medication (allopathic medicines directly purchased from pharmacy or giving home remedies available at home) when compared to rural parents which was 8% (p<0.001) and in a similar study done by Minhas et al reported 33% in rural and 30% in urban areas. 4 In our study 53% and 1% in urban and rural areas preferred to wait and watch before taking steps to control illness contradict study done by Minhas et al who reported 16.91% and 15.32% in urban and rural areas and another study done by Haresh Chandwani reported 27.9%. 4,11 Interestingly only 1% of urban parents took their children to quacks also known as RMP (rural medical practioner) in Andhra Pradesh when compared to 55% from rural area (p<0.001).…”
Section: Resultscontrasting
confidence: 71%
See 3 more Smart Citations
“…10 Majority from urban 87% practiced self-medication (allopathic medicines directly purchased from pharmacy or giving home remedies available at home) when compared to rural parents which was 8% (p<0.001) and in a similar study done by Minhas et al reported 33% in rural and 30% in urban areas. 4 In our study 53% and 1% in urban and rural areas preferred to wait and watch before taking steps to control illness contradict study done by Minhas et al who reported 16.91% and 15.32% in urban and rural areas and another study done by Haresh Chandwani reported 27.9%. 4,11 Interestingly only 1% of urban parents took their children to quacks also known as RMP (rural medical practioner) in Andhra Pradesh when compared to 55% from rural area (p<0.001).…”
Section: Resultscontrasting
confidence: 71%
“…4 In our study 53% and 1% in urban and rural areas preferred to wait and watch before taking steps to control illness contradict study done by Minhas et al who reported 16.91% and 15.32% in urban and rural areas and another study done by Haresh Chandwani reported 27.9%. 4,11 Interestingly only 1% of urban parents took their children to quacks also known as RMP (rural medical practioner) in Andhra Pradesh when compared to 55% from rural area (p<0.001). In another study done by Mandalik et al found 0.6% from urban area approached quacks and Minhas et al reported 12.9% in rural and 5% in urban areas.…”
Section: Resultscontrasting
confidence: 71%
See 2 more Smart Citations
“…Primary care was measured using the question “where do you usually go to seek health services when you sick?” with answer options of 1 = “community health service center/township health center,” 2=“community health service station/village clinic,” 3 = “clinic,” 4 = “general hospitals,” and 5 = “specialty hospitals.” Considering whether residents go to primary care facilities is to measure the implementation effects of major measures such as China's deepening reform planning and implementation scheme as of medical and health ( 11 , 12 ). According to national standards, community health service center/township health center/community health service station/village clinic are defined as primary medical facilities.…”
Section: Methodsmentioning
confidence: 99%